Beyond Traditional Listening Instruction: A Mixed-Methods Study on the Impact of VOA Learning English on EFL Learners’ Motivation and Listening Proficiency - Arif Eko Wahyudi; Bachtiar Bachtiar; Ahmad Heki Sujiatmoko (Universitas Pahlawan Tuanku Tambusai, 2026)
Grounded in Self-Determination Theory (SDT), which identifies autonomy, competence, and relatedness as core drivers of intrinsic motivation, this study examines the effectiveness of VOA Learning English in enhancing EFL learners’ listening comprehension and motivation. A sequential explanatory mixed-methods design was employed, combining a quasi-experimental pre-test and post-test control group design with semi-structured interviews. Seventy tenth-grade students from a public senior high school in Anambas Regency, Indonesia, were assigned to either an experimental group using VOA Learning English or a control group receiving conventional instruction; six students were purposefully selected for the qualitative phase. Results showed that the experimental group achieved a significantly greater improvement in listening comprehension (pre-test M = 44.00; post-test M = 76.00) than the control group, supported by statistically significant between-group differences (t = -3.077, p = .003). Motivation scores were also uniformly high (M = 4.28), spanning intrinsic, extrinsic, integrative, and instrumental dimensions. Qualitatively, students across all proficiency levels reported positive learning experiences, citing the transcript and replay features as particularly effective scaffolding tools. These findings indicate that VOA Learning English is a pedagogically sound and inclusive instructional tool, with implications for the broader integration of mobile-assisted platforms into EFL curricula.